(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Any translation practice is intended to produce a text which is equivalent in meaning with its source text. However, to arrive at such equivalence is not an easy task due to a number of differences between the source language and the target language. Therefore, finding the right equivalence is a problem often encountered by translators. Suggested by such problem, a study on equivalence problems and possible strategies to solve the problems is obviously necessary. This article aims at finding out the problems of equivalence encountered English-Uzbek translation and to analyze effective strategies to solve such problems. The study is based on comparative analysis of linguistic and cultural features of both languages, including lexical, grammatical, and stylistic differences